ANALISIS PENERAPAN LEAN MANUFACTURING DAN 5S DI PT ATLANTIC ANUGRAH METALINDO MENGGUNAKAN METODE VSM - Juwita, Abelia Dhuwi; Cattleya Prameswari Anissa Islami, Mega (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study aims to analyze the implementation of Lean Manufacturing and the 5S method at PT Atlantic Anugrah Metalindo, a company engaged in the production of custom metal products. In the era of increasingly intense industrial competition, the company faces challenges in improving productivity and product quality. The method used in this research is Value Stream Mapping (VSM) to map the production process flow and identify areas that require improvement. Data were collected through direct observation, interviews with employees, and the analysis of related documentation. The results of the study indicate that the implementation of Lean Manufacturing and 5S can reduce waste, improve efficiency, and shorten lead time, ultimately contributing to improved production performance and customer satisfaction.